2014
DOI: 10.17221/820/2013-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tillage practices and rate of nitrogen fertilization on crop yield and soil carbon and nitrogen

Abstract: We conducted field experiments since 2006 to determine the effect of tillage practices and rate of nitrogen fertilization on soil properties and crop yield. Four tillage practices and five N rates were used. The results showed that the year-round total yield of wheat and maize under harrow tillage (HT) and rotary tillage (RT) was not significantly different from that of conventional tillage (CT, moldboard tillage) but was higher than that of no-tillage (NT). Reduced tillage (HT and RT) with straw returned and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
7
9
0
Order By: Relevance
“…Higher SOC in the surface 0-5 cm soil layer observed in our study is in conformity with previous studies which showed surface-layer (0-5 cm) increments of SOC content in NT than RT [8,28,43,44]. The increase in SOC concentration with reversal of tillage was closely associated with enhanced decomposition of incorporated crop residues.…”
Section: Soil Properties and Nutrient Availabilitysupporting
confidence: 92%
“…Higher SOC in the surface 0-5 cm soil layer observed in our study is in conformity with previous studies which showed surface-layer (0-5 cm) increments of SOC content in NT than RT [8,28,43,44]. The increase in SOC concentration with reversal of tillage was closely associated with enhanced decomposition of incorporated crop residues.…”
Section: Soil Properties and Nutrient Availabilitysupporting
confidence: 92%
“…Li et al (2007) showed that the available N, P, and K decreased with an increase in the soil bulk density in the deep soil layers, and deep tillage promoted the growth and accumulation of dry matter in maize during the late part of the growth stage. Feng et al (2014) indicated that harrow tillage and rotary tillage could adjust the soil C and N conditions for the winter wheat-summer maize cropping system. In the present study, with respect to cotton growth and development, as the soil replacement plus subsoiling treatment replaced the topsoil from 0 to 20 with the subsoil from 20 to 40 cm, the soil nutrients and microbial activity of the topsoil were poorer, thus delaying the cotton growth during the seedling and square formation stage compared with the growth stages under conventional rotary tillage.…”
Section: Discussionmentioning
confidence: 99%
“…The winter wheat–summer maize double cropping system is the main cropping pattern in the Huang‐Huai‐Hai region, one of the most important crop production regions in China (Feng et al, ) producing approximately 45% of China's total cereal production (Fang et al, ). However, agricultural water shortages and how to solve these problems have become burning issues in recent years (Brown and Halweil, ).…”
Section: Introductionmentioning
confidence: 99%